2017
DOI: 10.1039/c7ra06701a
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of cellulose rich municipal solid waste blends using ionic liquids: feedstock convertibility and process scale-up

Abstract: Sixteen cellulose rich municipal solid waste (MSW) blends were developed and screened using an acidassisted ionic liquid (IL) deconstruction process. Corn stover and switchgrass were chosen to represent herbaceous feedstocks; non-recyclable paper (NRP) and grass clippings (GC) collected from households were chosen as MSW candidates given their abundance in municipal waste streams. The most promising MSW blend: corn stover/non-recyclable paper (CS/NRP) at 80/20 ratio was identified in milliliter-scale screening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Non‐air‐classified and air‐classified grass clippings were both ground to 2 mm by using a Wiley Mill. The nonrecyclable fraction of MSW‐derived paper was collected by Cascadia Consulting (Seattle, WA) during a waste composition study conducted in the City of Seattle in July and November 2014 . The nonrecyclable components consisted of aseptic and polycoated containers and packaging, food‐soiled paper, shredded paper, and waxed or coated papers and cardboard.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Non‐air‐classified and air‐classified grass clippings were both ground to 2 mm by using a Wiley Mill. The nonrecyclable fraction of MSW‐derived paper was collected by Cascadia Consulting (Seattle, WA) during a waste composition study conducted in the City of Seattle in July and November 2014 . The nonrecyclable components consisted of aseptic and polycoated containers and packaging, food‐soiled paper, shredded paper, and waxed or coated papers and cardboard.…”
Section: Methodsmentioning
confidence: 99%
“…The nonrecyclable fraction of MSW-derived paper was collected by Cascadia Consulting (Seattle, WA)d uring aw aste composition study conducted in the City of Seattle in July and November 2014. [26] The nonrecyclable components consisted of aseptic and polycoated containers and packaging, food-soiled paper,s hredded paper,a nd waxed or coated papers and cardboard. These materials were dried to < 10 %m oisture and shredded with aF ranklin Miller Ta skmaster commercial-scale shredder (Franklin Miller,L ivingston, NJ) and then further size-reduced to 2mmb yu sing aW iley Mill.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study concluded that phosphonium-based ILs are better extractants than the traditional organic solvents for recovery of short chain organic acids from aqueous dilute solutions. They succeeded to obtain higher distribution coefficients as compared to most traditional solvents by using phosphonium-based ionic liquids for the extraction of low concentrated lactic acid solutions, and obtained an extraction efficiency of 98.4% with a two-step extraction (Liang et al, 2017;Oliveira et al, 2012). IL-mediated esterification for reactive extraction of low-value VFA from dilute aqueous streams was also reported.…”
Section: Altering the Ad Platform For Higher Organic Carbon Product C...mentioning
confidence: 99%